Cotton cleaner with multifaceted grates - Mirzaumidov, Asilbek; Nurillaeva , Khosiyat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Based on the experiments carried out with a change in the number of sides of the grate in the area of pulling raw cotton, it has a sinusoidal shape relative to the faces of the grate, with different angles of location, which leads to the release of impurities of different masses and different depths in the cotton. Multi-faceted grates can hold the most loosely attached cotton flakes, which leads to repeated and uniform unloading on the teeth of the saw drum. Multi-faceted grates can hold the most loosely attached cotton flakes, which leads to repeated and uniform unloading on the teeth of the saw drum.